2011
DOI: 10.1088/0957-4484/23/2/025703
|View full text |Cite
|
Sign up to set email alerts
|

Influence of microstructures on mechanical behaviours of SiC nanowires: a molecular dynamics study

Abstract: The tensile behaviours of [111]-oriented SiC nanowires with various microstructures are investigated by using molecular dynamics simulations. The results revealed the influence of microstructures on the brittleness and plasticity of SiC nanowires. Plastic deformation is mainly induced by the anti-parallel sliding of 3C grains along an intergranular amorphous film parallel to the (111) plane and inclined at an angle of 19.47 • with respect to the nanowire axis. Our study suggests that the wide dispersion of mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 38 publications
8
44
1
Order By: Relevance
“…The measured strength values of SiC NWs with stacking faults are much lower than the theoretical prediction of 53.4 GPa for single crystal SiC. This suggests that twins and stacking faults decreased the strength of SiC NWs, supported by the previous simulation 204. Nevertheless, it is still unclear that whether or not such weakening effect of stacking faults prevails in other ceramic NWs.…”
Section: Mechanical Characterization Of Nwssupporting
confidence: 52%
See 1 more Smart Citation
“…The measured strength values of SiC NWs with stacking faults are much lower than the theoretical prediction of 53.4 GPa for single crystal SiC. This suggests that twins and stacking faults decreased the strength of SiC NWs, supported by the previous simulation 204. Nevertheless, it is still unclear that whether or not such weakening effect of stacking faults prevails in other ceramic NWs.…”
Section: Mechanical Characterization Of Nwssupporting
confidence: 52%
“…twining plane perpendicular to the growth direction) 277. The systematic MD simulation on SiC NWs indicated that the pure 3C‐structure of SiC was the strongest with a strength of 28.5 GPa, the highly defective structure was the second strongest, and the 3C structure with 19.47° stacking faults was the weakest 204. This agrees well with the in situ SEM tensile test of SiC NWs, which revealed that cracks always initiated and propagated in the 3C segments with 19.47° stacking faults, giving a maximum tensile strength of 25.3 GPa 233.…”
Section: Mechanical Characterization Of Nwsmentioning
confidence: 99%
“…More details of the numerical simulations are provided in Ref. [22]. Due to the slight tapering in the pillar, a model was derived to estimate the Young's modulus E of a tapered pillar based on the linear load-displacement record.…”
Section: Methodsmentioning
confidence: 99%
“…With the advancement of materials processing technology, micro-and nanoscale SiC components can be easily produced and they demonstrate promising applications in micro-and nanoelectromechanical systems [19]. Available reports indicate that nanoscale SiC shows large plastic deformation through lattice breakage, lattice disorder and amorphization [20][21][22]. Phase transformation, which may also introduce plastic deformation, has been observed in SiC during annealing [23], thermal oxidation [24] and stressing at high temperature [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Since relatively smooth fracture surfaces can be realized in structures with ultrathin lateral dimensions, it seems that self-healing may be an intrinsic property of one-dimensional nanomaterials [11][12][13][14][15]. However, self-healing has rarely been observed in GaAs NWs with lateral dimensions more than 12 nm.…”
Section: Introductionmentioning
confidence: 99%